The impact of TSH levels on clinical outcomes 14 days after frozen-thawed embryo transfer - Yuchao Zhang; Wenbin Wu; Yanli Liu; Yichun Guan; Xingling Wang; Liting Jia (BMC, 2020)
Abstract Background The aim of this study was to investigate the impact of TSH levels on clinical outcomes 14 days after frozen-thawed embryo transfer. Methods Blood samples were collected on the first visit to our department and 14 days after embryo transfer. Women were divided into three groups based on D14 TSH levels, which were compared to basal TSH levels in groups with different clinical outcomes. TSH levels between pregnant and nonpregnant women were also compared. Results The clinical pregnancy rate in women with lower TSH levels 14 days after transfer was slightly but significantly lower (56%, P = 0.05) compared to those with higher TSH levels. Furthermore, TSH levels were significantly elevated 14 days after transfer compared to basal TSH levels in pregnant women and in women who successfully became pregnant (P < 0.001, respectively). Conclusions Elevated TSH levels 14 days after embryo transfer compared to basal TSH levels seem to play a protective role and predict favorable clinical outcomes under specific conditions.